In vivo and in vitro Evaluation of Cytokine Expression Profiles During Middle East Respiratory Syndrome Coronavirus (MERS-CoV) Infection - Mubarak A (Dove Medical Press, 2021)
Ayman Mubarak,1 Bahauddeen Alrfaei,2 Abdullah Aljurayyan,3 Mahfoudh M Alqafil,1 Mohamed A Farrag,1 Maaweya E Hamed,1 Bandar Alosaimi,4 Fahad Almajhdi,1 Wael Alturaiki5 1Department of Botany and Microbiology, College of Science, King Saud University, Riyadh, Saudi Arabia; 2Stem Cells Unit, Department of Cellular Therapy, King Abdullah International Medical Research Center, King Saud Bin Abdulaziz University for Health Science, MNGHA, Riyadh, Saudi Arabia; 3Immunology and HLA Department, Pathology and Laboratory Medicine, King Fahad Medical City, Riyadh, Saudi Arabia; 4Research Center, King Fahad Medical City, Riyadh, Saudi Arabia; 5Department of Medical Laboratory Sciences, College of Applied Medical Sciences, Majmaah University, Majmaah, 11952, Saudi ArabiaCorrespondence: Wael AlturaikiDepartment of Medical Laboratory Sciences, College of Applied Medical Sciences, Majmaah University, Majmaah, 11952, Saudi ArabiaEmail w.alturaiki@mu.edu.saBackground: Middle East respiratory syndrome coronavirus (MERS-CoV) first emerged in the Kingdom of Saudi Arabia, is associated with a high mortality rate.Aim: To determine the effect of MERS-CoV on the immune response in infected patients and investigate cytokine production in the A549 epithelial cell line in response to a recombinant MERS-CoV spike protein (rSP) in the presence or absence of anti-dipeptidyl peptidase 4 (DPP4) antibody (3 independent experiments). Cytokine levels were measured using a cytokine ELISA array.Methods: A Bio-Plex multiplex assay and cytokine ELISA were used in our study to measure the cytokine levels.Results: Comparative analysis of MERS-CoV-infected patients (4 samples) and noninfected healthy controls (HCs) (5 samples) showed that serum levels of the following cytokines and chemokines were significantly higher in MERS-CoV patients than in the HCs (*p < 0.05): interferon (IFN)-α 2 (43.4 vs 5.4), IFN-β (17.7 vs 6.2), IFN-γ (43.4 vs 9.7), interleukin (IL)-8 (13.7 vs 0), IL-2 (11.2 vs 3), IL-27p28 (57.8 vs 13.8), and IL-35 (167.5 vs 87.5).Discussion: Our results revealed that MERS-CoV infection induced a slight increase in IFN levels but triggered a more pronounced increase in expression of the regulatory cytokines IL-27 and IL-35. A recombinant version of the full-length MERS-CoV spike protein increased the expression of IL-8 (160 pg/mL), IL-2 (100 pg/mL) and IL-12 (65 pg/mL) in A549 lung epithelial cells compared to that in the unstimulated control cells. The presence of anti-DPP4 antibody did not affect cytokine suppression or induction in A549 cells in vitro but decreased the level of IL-8 from 160 pg/mL to 65 pg/mL.Conclusion: MERS-CoV can decrease IFN levels to interfere with the IFN pathway and enhance the production of regulatory cytokines. Inhibition of the increases in IL-27 and IL-35 may contribute to halting MERS-CoV in the early stage of infection.Keywords: MERS-CoV, proinflammatory cytokines, regulatory cytokines, anti-DPP4, IFNs, A549 lung cells